Edukasi Kesehatan Ibu Dan Anak Berbasis E-Book Sebagai Inovasi Pengabdian Masyarakat: Edukasi Kesehatan Ibu Dan Anak Berbasis E-Book Sebagai Inovasi Pengabdian Masyarakat - Ekayanti Ekayanti; Jusmawati Jusmawati; Ade Sri Wahyuningsih (Sekolah Tinggi Ilmu Kesehatan Gunung Sari, 2025)
Maternal and child health is an important indicator of community health development. Limited maternal knowledge regarding pregnancy, childbirth, postpartum care, breastfeeding, and infant care remains a public health concern. This community service activity aimed to improve maternal knowledge through e-book-based health education. The activity was conducted at the Tanah Lemo Village Office, Bontobahari District, Bulukumba Regency, involving 27 respondents. The methods included e-book development, health education sessions, interactive discussions, and evaluation. The results showed an increase in participants’ knowledge, particularly regarding pregnancy danger signs, antenatal care, exclusive breastfeeding, and infant care. The e-book was considered effective due to its accessibility and sustainability. In conclusion, e-book-based education positively contributes to improving maternal and child health literacy